2004
DOI: 10.1142/s0218810404001929
|View full text |Cite
|
Sign up to set email alerts
|

Toe-to-Hand Transfer in Symbrachydactyly

Abstract: Symbrachydactyly, or central atypical cleft, is classified as a failure of formation. For the adactylous or monodactylous forms, free toe transfer is the treatment of choice. We present 18 free toe transfers in 13 patients for symbrachydactyly. Despite abnormal anatomy, the functional building blocks have always been available and transfer technically possible. The result has been improved function and high levels of parental satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Yoshimura [42] reported 33 pediatric toe transfers in 28 children, 2 of whom had congenital anomalies—one child had an absent thumb, index, and middle fingers and the second child had congenital constriction ring syndrome. After other case reports [24, 27], several surgeons have reported larger series of microsurgical toe-to-hand transfers to reconstruct various congenital anomalies of the hand [3, 10–13, 15, 1720, 30, 31, 36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…Yoshimura [42] reported 33 pediatric toe transfers in 28 children, 2 of whom had congenital anomalies—one child had an absent thumb, index, and middle fingers and the second child had congenital constriction ring syndrome. After other case reports [24, 27], several surgeons have reported larger series of microsurgical toe-to-hand transfers to reconstruct various congenital anomalies of the hand [3, 10–13, 15, 1720, 30, 31, 36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…At 5-year follow-up, range of motion (ROM) was adequate, and most participants reported that they used the affected hand in daily activities. In 2004, Richardson 53 described the results of 18 free toe transfers in 13 patients with symbrachydactyly. The results of a bimanual hand function questionnaire indicated that 61% could lift a cup, 54% could button, 38% could cut paper, and 30% could use a knife and fork; 85% of parents were happy with the appearance of the hand and 77% were happy with the function of the hand.…”
Section: Syndactyly and Web Contracturementioning
confidence: 99%
“…Others have reinforced that there is a wide variation in the neurovascular structures in symbrachydactyly. 35,40,53 In 2001, Foucher 18 reported on 51 toe transfers in 45 patients with symbrachydactyly. Transfers to types IIIA and IIIB were the most common, followed by type IVA.…”
Section: Syndactyly and Web Contracturementioning
confidence: 99%
“…Congenital thumb absence, constriction ring syndrome, and symbrachydactyly are now potential indications for toe-hand transfer in order to restore sensate pinch. (18-19) Although early attempts were met with concern for epiphyseal disruption and premature closure, more recent series indicate that toes transferred to the hand in children can reach up to 100% length of the contralateral toe and with normal growth. (20)…”
Section: Evolving Indicationsmentioning
confidence: 99%